QUO VADIS PENDIDIKAN MULTIKULTURAL DALAM ERA GLOBAL DI PESANTREN - Moh Miftahul Choiri (Cendekia: Kependidikan dan Kemasyarakatan, 2011)
Historically, schools are educational institutions that are identical to the meaning of the typical Islamic Indonesia. As an educational institution "native Indonesia", boarding schools have a strong influence in shaping and maintaining social, cultural, political and religious people of Indonesia, especially Java, because the term evolved pesantren in Java. In the era of globalization, there is a contradiction between the global and local values. Form of opposition, including the cultural uniformity which is controlled by the big nations and developed nations such as Europe and the United States. Therefore, schools as institutions of traditional Islamic education in Indonesia has the challenge of playing a role in welcoming the era of globalization, especially to guard the positive cultures of traditional Islam which is rooted in the community, especially the local culture. Through multicultural education, schools are expected to see the urgency of the culture that had been developed in the community, particularly the Muslim community and bridging the cultural problem that is increasingly worrying.تاريخيا، والمدارس والمؤسسات التعليمية التي هي مطابقة لمعنى إندونيسيا الإسلامية النموذجية. باعتباره "اندونيسيا الأم" المؤسسة التعليمية، والمدارس الداخلية لها تأثير قوي في تشكيل والحفاظ على الناس الاجتماعية والثقافية والسياسية والدينية في اندونيسيا، وخصوصا جاوة ، لأن مصطلح تطورت المدارس الإسلامية الداخلية في جاوا. في عصر العولمة ، هناك تناقض بين القيم العالمية والمحلية. شكل من أشكال المعارضة ، بما في ذلك التماثل الثقافي الذي تسيطر عليه الدول الكبرى والدول المتقدمة مثل أوروبا والولايات المتحدة. ولذلك، والمدارس ومؤسسات التعليم الإسلامي التقليدي في إندونيسيا والتحدي المتمثل في لعب دور في الترحيب عصر العولمة، لا سيما لحراسة ثقافات إيجابية عن الإسلام التقليدي المتجذر في المجتمع، وبخاصة الثقافة المحلية. من خلال التعليم متعدد الثقافات ، ومن المتوقع أن المدارس لمعرفة الحاجة الملحة للثقافة التي تم وضعها في المجتمع، ولاسيما المجتمع مسلم وردم المشكلة الثقافية التي تبعث على القلق بشكل متزايد